A method for separating gallium and germanium from zinc slag and purifying gallium

By combining tartaric acid complexing agent and anion exchange resin, the problems of low adsorption capacity and serious environmental pollution in the separation and purification of gallium and germanium in zinc slag were solved, and efficient and environmentally friendly gallium recovery was achieved, which is suitable for large-scale industrial production.

CN120350254BActive Publication Date: 2025-09-19GUANGXI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510847440.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-24
Publication Date
2025-09-19
Estimated Expiration
2045-06-24

AI Technical Summary

Technical Problem

The existing technology for separating and purifying gallium from zinc slag has problems such as low adsorption capacity, poor selectivity, poor cycle performance and severe environmental pollution, making it difficult to efficiently recover gallium and germanium resources.

Method used

Tartaric acid is used as a complexing agent in combination with anion exchange resin. By adjusting the pH value of the solution and using iron powder for reduction, selective adsorption and desorption of gallium and germanium are achieved, and macroporous strong alkaline styrene resin is used for multiple recycling.

Benefits of technology

The separation and purification of high-concentration gallium solutions is achieved, the gallium recovery efficiency is improved, the cost is reduced, the process complies with the environmental protection requirements of green chemistry, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120350254B_ABST
    Figure CN120350254B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for separating gallium and germanium from zinc slag and purifying gallium, belonging to the field of separation and purification technology. The method comprises using tartaric acid as a complexing agent, adjusting the pH of a zinc slag leachate containing gallium and germanium to achieve selective coordination between the tartaric acid and metal ions, adsorbing the coordination complex using a macroporous, strongly basic styrene-based anion exchange resin, sequentially separating germanium and gallium from the zinc slag leachate, and then eluting the adsorbent resin with an eluent to obtain a high-concentration gallium-containing solution. The present invention utilizes the above-mentioned method for separating gallium and germanium from zinc slag and purifying gallium, which has strong selectivity, mild conditions, simple operation, good cycle performance, and low environmental pollution. It can not only address the harm caused to the ecological environment by the accumulation of secondary resource zinc slag, but also solve the problem of resource shortage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of separation and purification, and in particular to a method for separating gallium and germanium from zinc slag and purifying gallium. Background Art

[0002] With the rapid development of technologies such as semiconductor materials, new energy, 5G communications, and aerospace, global consumption of rare earth metals has increased annually. Gallium and germanium play a crucial role in modern technology. Gallium's low melting point makes it an ideal material for devices like high-temperature thermometers and thermistors, earning it the nickname "the new food of the semiconductor industry." Germanium, on the other hand, is a core raw material for semiconductor production. Gallium and germanium, combined with other elements, can improve the transmission speed and efficiency of semiconductors. Against this backdrop, the resource development and industrial development of gallium and germanium face new opportunities and challenges.

[0003] Besides gallium extracted from Bayer mother liquor, zinc slag is the second largest source of gallium. Currently, gallium recovered from zinc slag accounts for 10% of global gallium production. Recovering and purifying gallium from secondary resources can effectively alleviate resource shortages and has important economic significance.

[0004] Currently, the main methods for separating and purifying gallium from zinc slag include reduction roasting-magnetic separation, extraction, membrane separation, and adsorption. Adsorption is the most widely used method due to its advantages of high separation efficiency, minimal equipment requirements, and simple operation. Ion exchange resins are complex organic polymers with a network structure, and their separation principle is primarily ion exchange. Ion exchange reactions are generally reversible equilibriums, which allows the resins to be regenerated and reused, achieving efficient separation and purification.

[0005] Tartaric acid is a strong chelating agent, containing two carboxyl groups within its molecule. These groups have the ability to donate electron pairs, forming coordination bonds with metal ions. Furthermore, the presence of two asymmetric carbon atoms within the tartaric acid molecule results in the existence of two spatially distinct isomers. This asymmetric structure increases the potential for complex formation between tartaric acid and metal ions, making tartaric acid valuable for a wide range of applications. Leveraging the strong chelating ability of tartaric acid and the excellent adsorption and selectivity of ion exchange resins, the selective separation of gallium and germanium from sulfuric acid-leached zinc slag solutions can effectively mitigate the shortage of gallium and germanium raw materials.

[0006] Currently, there are patents that study the use of adsorbents to recover gallium from solutions. Patent CN118955996A discloses a method for preparing a microporous chelating resin based on cage-type polysesquioxane-modified gallium adsorption. Although the use of cage-type polysesquioxane modification can improve the strength of the chelating resin, and the chelating resin has high selectivity for metal ions, high adsorption capacity, good stability, and reproducibility, the preparation process is complex and the organic reaction easily produces byproducts that affect the yield, increasing time and cost, which is not conducive to industrialization. Patent CN118359746A discloses a method for preparing a hydroxamic acid-functionalized gallium ion adsorption resin, a gallium ion adsorption resin, and its application. The addition of glycine causes the adsorbent to form a stable complex with the metal ion, but the saturated adsorption capacity is low and it has a certain adsorption capacity for iron. The subsequent iron precipitation requires multiple times, which is a cumbersome process. Patent CN102433435A discloses an extractant and method for extracting gallium and germanium. While this method provides an extractant with excellent extraction performance, strong selectivity, high extraction rate, and good phase separation properties, the extraction process inevitably uses a large amount of organic solvent, which poses significant environmental hazards. The extractant is also difficult to completely separate from the solution, significantly impacting subsequent electrolytic recovery. Furthermore, the pH for both adsorption and extraction is less than 3; above 3, gallium is lost through co-precipitation with other metal ions.

[0007] In addition, in the sulfuric acid leaching zinc slag solution, multiple ions coexist, and the content of gallium and germanium is relatively low. The existing adsorption materials have problems such as low adsorption capacity, poor selectivity, and poor cycle performance. Summary of the Invention

[0008] The present invention provides a method for separating gallium from germanium and purifying gallium from zinc slag. Tartaric acid is used as a complexing agent in combination with an anion exchange resin to selectively adsorb gallium and produce a highly concentrated gallium-containing solution. This method boasts strong selectivity, mild conditions, simple operation, excellent recycling performance, and minimal environmental pollution. It can address the ecological hazards posed by the accumulation of secondary zinc slag and address resource shortages. Furthermore, tartaric acid-coordinated gallium surpasses the traditional adsorption pH range, expanding the pH range for gallium extraction to 3 to 9.

[0009] To achieve the above object, the present invention provides a method for separating gallium and germanium from zinc slag and purifying gallium, comprising the following steps:

[0010] S1. Adding a complexing agent to a gallium-germanium-containing leachate, adjusting the pH value, and then adding iron powder;

[0011] S2. Using a peristaltic pump, the gallium-germanium-containing leachate to which the iron powder has been added is pumped into an adsorption column filled with an adsorption resin for adsorption, thereby obtaining a gallium-containing mixed solution;

[0012] S3, using an eluent to desorb the adsorption resin after adsorption in S2, and the desorbed adsorption resin is washed with alkaline water and neutralized, and recycled;

[0013] S4, adjusting the pH of the gallium-containing mixed solution obtained in S2 with NaOH, adding a complexing agent, and then using a peristaltic pump to pump the gallium-containing mixed solution after the complexing agent is added into an adsorption column filled with the adsorption resin neutralized in S3 for adsorption;

[0014] S5, using an eluent to desorb the adsorption resin after adsorption in S4, separating and obtaining a gallium-containing solution, and significantly improving the gallium purity;

[0015] The adsorption resin after desorption in S6 and S5 is neutralized by washing with alkaline water and recycled.

[0016] Preferably, in S1, the gallium-germanium-containing leachate is obtained by crushing and grinding zinc slag and then digesting it with dilute sulfuric acid.

[0017] Preferably, in S1, the complexing agent is tartaric acid, and the molar ratio of the complexing agent to the germanium in the gallium-germanium-containing leachate is (1-2):1.

[0018] Preferably, in S1, the specific operation of adjusting the pH value is: using dilute sulfuric acid and sodium hydroxide solution to adjust the pH value of the mixed solution to 1-2.5.

[0019] Preferably, in S2, the adsorption resin is a macroporous, strongly basic styrene-based anion exchange resin containing quaternary ammonia.

[0020] Preferably, in S2 and S4, the adsorption temperature is room temperature and the adsorption time is 2 to 4 hours.

[0021] Preferably, in S4, the pH value of the gallium-containing mixed solution is adjusted to 3-9, and the molar ratio of the complexing agent to gallium in the gallium-containing mixed solution is (1-1.5):1.

[0022] Preferably, in S3 and S5, the eluent is one of hydrochloric acid, sulfuric acid, nitric acid, and ammonium chloride.

[0023] Preferably, in S3 and S5, the eluent is 0.1-2 mol / L HNO3.

[0024] Therefore, the present invention adopts the above-mentioned method for separating gallium and germanium from zinc slag and purifying gallium, which has the following beneficial effects:

[0025] (1) Utilizing the strong complexing ability of tartaric acid and the good adsorption and selectivity of ion exchange resin, gallium and germanium are selectively separated from the sulfuric acid leached zinc slag solution, and the ion exchange resin after adsorption of gallium is desorbed to obtain a high-concentration gallium-containing solution;

[0026] (2) The macroporous, strongly basic styrene-based anion exchange resin containing quaternary ammonia has a high adsorption capacity and can process a large amount of secondary resources - zinc slag in a short time, thereby improving the recovery efficiency of gallium. In addition, the used ion exchange resin can be restored to its adsorption capacity through appropriate regeneration methods (such as acid washing and alkaline washing), enabling multiple uses and reducing costs.

[0027] (3) The ion exchange resin adsorption process has strong selectivity, simple operation, mild conditions, easy control, little pollution to the environment, and good recycling performance. It conforms to the concept of green chemistry and is suitable for large-scale industrial production. It can not only solve the harm caused by the accumulation of secondary resource zinc slag to the ecological environment, but also solve the problem of resource shortage.

[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a graph showing the saturated adsorption capacity of D201 resin for gallium in a method for separating gallium and germanium from zinc slag and purifying gallium according to the present invention;

[0030] Figure 2 This is a diagram showing the effects of solution pH and tartaric acid dosage on the selective adsorption of Ga(III) and Ge(IV) in a method for separating gallium and germanium from zinc slag and purifying gallium in the present invention;

[0031] Figure 3 This is a graph showing the selective adsorption of Ge(IV) by D201 resin in Example 1 of a method for separating gallium and germanium from zinc slag and purifying gallium according to the present invention;

[0032] Figure 4 This is a graph showing the selective adsorption of Ga(III) by D201 resin in Example 1 of a method for separating gallium and germanium from zinc slag and purifying gallium according to the present invention;

[0033] Figure 5 This is a graph showing the selective adsorption of Ge(IV) by D201 resin in Example 2 of a method for separating gallium and germanium from zinc slag and purifying gallium according to the present invention;

[0034] Figure 6 This is a graph showing the selective adsorption of Ga(III) by D201 resin in Example 2 of a method for separating gallium and germanium from zinc slag and purifying gallium according to the present invention;

[0035] Figure 7 This is a D201 resin cycle performance test chart for a method of separating gallium and germanium from zinc slag and purifying gallium in the present invention. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described below with reference to the accompanying drawings and embodiments.

[0037] Unless otherwise defined, technical or scientific terms used in the present invention shall have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs.

[0038] In existing research, the saturated adsorption capacity of germanium by macroporous strong basic styrene anion exchange resin (D201 resin) containing quaternary ammonia is 212.1 mg / g. Figure 1 As shown, a gallium-containing solution was obtained through a column adsorption test, and the Ga(III) concentration in the solution before and after adsorption was measured at different adsorption temperatures and different gallium concentrations. The saturated adsorption capacity of D201 resin for gallium was calculated to be 137.59 mg / g at 328 K and an initial gallium concentration of 1000 mg / L.

[0039] In the solution, both Ga(III) and Ge(IV) can react with tartaric acid to form complexes. By changing the pH of the solution and the amount of tartaric acid added, we observed whether D201 resin could achieve the separation of Ga(III) and Ge(IV). The results are as follows: Figure 2 As shown, Figure 2 (a) is the study of the adsorption performance of D201 resin for Ga(III) and Ge(IV) when the molar ratio of tartaric acid to Ga(III) is 1:1. Figure 2 (b) is the study of the adsorption performance of D201 resin on Ga(III) and Ge(IV) when the amount of tartaric acid is the sum of the molar ratios of Ga(III) and Ge(IV). The results show that when the pH of the solution is low, the H + Higher concentrations lead to H + The activity of H increases, and the gallium and germanium cations in the solution compete with each other. Tartaric acid will preferentially complex with germanium, and D201 resin will preferentially adsorb germanium. As the pH of the solution increases, H + The concentration of H + The activity of the D201 resin gradually weakened, and competitive adsorption weakened. The D201 resin adsorbed both gallium and germanium, until its adsorption capacity for gallium was stronger than that for germanium. This shows that by controlling the pH of the solution and the amount of tartaric acid, Ge(IV) can be separated from the solution first, and then Ga(III), thereby achieving the separation of Ga(III) and Ge(IV).

[0040] Example 1

[0041] A method for separating gallium and germanium from zinc slag and purifying gallium comprises the following steps:

[0042] S1. Crushing and grinding the zinc slag, digesting it with dilute sulfuric acid in a microwave digester to obtain a gallium-germanium-containing leachate, adding tartaric acid as a chelating agent, the molar ratio of tartaric acid to germanium in the gallium-germanium-containing leachate being 1:1, adjusting the pH value to 2 using dilute sulfuric acid and sodium hydroxide solution, and adding excess nano-iron powder to reduce Fe(III) to Fe(II).

[0043] The zinc slag was produced in the actual production process of Guangxi Hechi Yusheng Company. The changes in metal ion concentrations in the gallium-germanium leaching solution, the gallium-germanium leaching solution after pH adjustment, and the gallium-germanium leaching solution after adding iron powder are shown in Table 1.

[0044] Table 1 Changes in metal ion concentrations in solutions at each stage

[0045] ;

[0046] S2. Use a peristaltic pump to pump 500 mL of the gallium-germanium leachate to which iron powder has been added into an adsorption column filled with 2.5 g of D201 resin. Adsorb at room temperature for 2 h to obtain a gallium-containing mixed solution.

[0047] The dynamic changes of metal ion concentration during adsorption are as follows: Figure 3 As shown. Under pH = 2, D201 resin has no adsorption effect on Fe(Ⅱ), and iron powder does not affect the adsorption performance of D201 resin for gallium. The concentration of Ge(IV) increased from 0.49 g / L to 20.81 g / L, with an enrichment coefficient of 42.67 (C / C0), while the concentration of Ga(III) did not change. The metal recovery rate during the dynamic adsorption process is shown in Table 2. The dynamic adsorption process is divided into three stages: stage I is the adsorption stage, stage II is the water washing stage, and stage III is the regeneration stage. The recovery rate of Ge(IV) in the regeneration stage is 97.20%, indicating that D201 resin can be used for the separation and enrichment of Ga(III) and Ge(IV) in zinc slag leachate.

[0048] Table 2 Metal recovery rates at each stage during dynamic adsorption

[0049] ;

[0050] S3: Desorb the D201 resin adsorbed in S2 using 2 mol / L HNO3. Almost no metal elements other than Ge were detected in the desorbed solution, with a Ge concentration of 20.81 g / L. The desorbed D201 resin was washed and neutralized with sodium hydroxide solution and recycled.

[0051] S4. The pH value of the gallium-containing mixed solution obtained in S2 was adjusted to 4 using NaOH, and tartaric acid was added at a molar ratio of 1:1 to gallium in the gallium-containing mixed solution. The gallium-containing mixed solution after the addition of tartaric acid was then pumped into an adsorption column containing D201 resin neutralized with S3 using a peristaltic pump for adsorption. The organic carbon content in the gallium-containing mixed solution after adsorption was almost zero, as shown in Table 3, indicating that the tartaric acid had been completely adsorbed into the resin, thereby preventing environmental pollution by organic acids.

[0052] Table 3 TOC content in the solution before and after adsorption and desorption

[0053] ;

[0054] S5, using an eluent to desorb the D201 resin adsorbed in S4 to obtain a gallium-containing solution, such as Figure 4 As shown in Figure 2, almost no metal elements other than Ga were detected in the gallium-containing solution. The concentration of Ga was 1.11 g / L, and the enrichment coefficient was as high as 198.21 ( C / C 0), indicating that D201 resin can be used for the separation and enrichment of Ga(III) in zinc slag leachate, and gallium is significantly purified.

[0055] The D201 resin desorbed in S6 and S5 is washed and neutralized with sodium hydroxide solution and can be recycled again. Example

[0056] A method for separating gallium and germanium from zinc slag and purifying gallium comprises the following steps:

[0057] S1. The zinc slag is crushed and ground, and then digested with dilute sulfuric acid in a microwave digester to obtain a gallium-germanium leaching solution. Tartaric acid is added as a complexing agent, and the molar ratio of tartaric acid to germanium in the gallium-germanium leaching solution is 1.2:1. The pH value is adjusted to 1.5 using dilute sulfuric acid and sodium hydroxide solution, and excess nano-iron powder is added to reduce Fe(III) to Fe(II).

[0058] Table 4 shows the changes in metal ion concentrations in the gallium-germanium leachate, the gallium-germanium leachate after pH adjustment, and the gallium-germanium leachate after adding iron powder.

[0059] Table 4 Changes in metal ion concentrations in solutions at each stage

[0060] ;

[0061] S2. Use a peristaltic pump to pump 500 mL of the gallium-germanium leachate to which iron powder has been added into an adsorption column filled with 2.5 g of D201 resin. Adsorb at room temperature for 2 h to obtain a gallium-containing mixed solution.

[0062] The dynamic change of metal ion concentration during adsorption is: Figure 5As shown, the dynamic adsorption process is divided into three stages: stage I is the adsorption stage, stage II is the water washing stage, and stage III is the regeneration stage. Under pH = 1.5, D201 resin has no adsorption effect on Fe(II), and iron powder does not affect the adsorption performance of D201 resin for gallium. The concentration of Ge(IV) increases from 0.49 g / L to 21.62 g / L, and the enrichment coefficient is 43.21 ( C / C 0), while the Ga(III) concentration remained unchanged. The metal recoveries during the dynamic adsorption process are shown in Table 5. The recovery of Ge(IV) was 98.13%, indicating that D201 resin can be used for the separation and enrichment of Ga(III) and Ge(IV) in zinc slag leachate.

[0063] Table 5 Metal recovery rates at each stage during dynamic adsorption

[0064] ;

[0065] S3: Desorb the D201 resin adsorbed in S2 using 2 mol / L HNO3. Almost no metal elements other than Ge were detected in the desorbed solution, with a Ge concentration of 21.62 g / L. The desorbed D201 resin was washed and neutralized with sodium hydroxide solution and recycled.

[0066] S4. The pH value of the gallium-containing mixed solution obtained in S2 was adjusted to 5 using NaOH, and tartaric acid was added at a molar ratio of 1.2:1 to gallium in the gallium-containing mixed solution. The gallium-containing mixed solution after the addition of tartaric acid was then pumped into an adsorption column containing D201 resin neutralized with S3 using a peristaltic pump for adsorption. The organic carbon content in the gallium-containing mixed solution after adsorption was almost zero, as shown in Table 6, indicating that all the tartaric acid had been adsorbed into the resin, thereby preventing environmental pollution by organic acids.

[0067] Table 6 TOC content in the solution before and after adsorption and desorption

[0068] ;

[0069] S5, using an eluent to desorb the D201 resin adsorbed in S4 to obtain a gallium-containing solution, such as Figure 6 As shown in Figure 2, almost no metal elements other than Ga were detected in the gallium-containing solution. The concentration of Ga was 1.31 g / L, and the enrichment coefficient was as high as 198.21 ( C / C 0), indicating that D201 resin can be used for the separation and enrichment of Ga(III) in zinc slag leachate, and gallium is significantly purified.

[0070] The D201 resin desorbed in S6 and S5 is washed and neutralized with sodium hydroxide solution and can be recycled again.

[0071] Cycling performance test of D201 resin

[0072] The Ga(III) concentration was set to 100 mg / L and pumped into the adsorption column filled with D201 resin using a peristaltic pump. The adsorption was carried out for 2 hours in a shaker at 298K and a speed of 140 rpm. 2 mol / L HNO3 was then used as the eluent to desorb the adsorbed D201 resin in a shaker at 298K and a speed of 140 rpm for 2 hours. The adsorption-desorption process was repeated 5 times. The concentration of Ga(III) in the solution and in the desorption liquid before and after each adsorption was measured using a plasma emission spectrometer. The adsorption and desorption rates of Ga(III) by D201 resin were calculated. The results are shown in Figure 2. Figure 7 As shown in the figure, the adsorption and desorption performance of D201 resin for Ga(III) did not change significantly, indicating that D201 resin has good reusability.

[0073] Therefore, the present invention adopts the above-mentioned method for separating gallium and germanium from zinc slag and purifying gallium, uses tartaric acid as a complexing agent, and combines it with an anion exchange resin to achieve selective adsorption of gallium and obtain a high-concentration gallium-containing solution. This method has strong selectivity, mild conditions, simple operation, good circulation performance, and low environmental pollution. It can not only solve the harm caused by the accumulation of secondary resource zinc slag to the ecological environment, but also solve the problem of resource shortage.

[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solutions of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for separating gallium and germanium from zinc slag and purifying gallium, characterized in that: The following steps are involved: S1, adding a complexing agent to the gallium-germanium leachate, adjusting the pH value and then adding iron powder; S2. Using a peristaltic pump, the gallium-germanium-containing leachate to which the iron powder has been added is pumped into an adsorption column filled with an adsorption resin for adsorption, thereby obtaining a gallium-containing mixed solution; S3, using an eluent to desorb the adsorption resin after adsorption in S2, and the desorbed adsorption resin is washed with alkaline water and neutralized, and recycled; S4, adjusting the pH of the gallium-containing mixed solution obtained in S2 with NaOH, adding a complexing agent, and then using a peristaltic pump to pump the gallium-containing mixed solution after the complexing agent is added into an adsorption column filled with the adsorption resin neutralized in S3 for adsorption; S5, using an eluent to desorb the adsorption resin after adsorption in S4, separating and obtaining a gallium-containing solution, and significantly improving the gallium purity; The adsorption resin after desorption in S6 and S5 is neutralized by washing with alkaline water and recycled; In S1, the complexing agent is tartaric acid, and the molar ratio of the complexing agent to the germanium in the gallium-germanium-containing leachate is (1-2):1; In S1, the specific operation of adjusting the pH value is: using dilute sulfuric acid and sodium hydroxide solution to adjust the pH value of the mixed solution to 1-2.5; In S4, the pH value of the gallium-containing mixed solution is adjusted to 3-9, and the molar ratio of the complexing agent to gallium in the gallium-containing mixed solution is (1-1.5):

1.

2. The method for separating gallium and germanium from zinc slag and purifying gallium according to claim 1, characterized in that: In S1, the gallium-germanium leaching solution is obtained by crushing and grinding zinc slag and then digesting it with dilute sulfuric acid.

3. The method for separating gallium and germanium from zinc slag and purifying gallium according to claim 1, characterized in that: In S2, the adsorption resin is a macroporous, strongly basic styrene-based anion exchange resin containing quaternary ammonia.

4. The method for separating gallium and germanium from zinc slag and purifying gallium according to claim 1, characterized in that: In S2 and S4, the adsorption temperature is room temperature and the adsorption time is 2~4h.

5. The method for separating gallium and germanium from zinc slag and purifying gallium according to claim 1, characterized in that: In S3 and S5, the eluent is one of hydrochloric acid, sulfuric acid, nitric acid, and ammonium chloride.

6. The method for separating gallium and germanium from zinc slag and purifying gallium according to claim 1, characterized in that: In S3 and S5, the eluent is 0.1~2mol / L HNO3.

Citation Information

Patent Citations

  • Extracting agent for extracting germanium and gallium and extraction method using same

    CN102433435A

  • Preparation method of hydroximic acid functionalized gallium ion adsorption resin, gallium ion adsorption resin and application

    CN118359746A

  • Preparation method of modified gallium-adsorbing microporous chelating resin based on polyhedral oligomeric silsesquioxane

    CN118955996A

  • Method of extracting gallium from aluminum chloride solution

    CN104018012A